2020
DOI: 10.1002/cmdc.202000419
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Passive Permeability in Designing Successful Drugs

Abstract: Passive permeability is a key property in drug disposition and delivery. It is critical for gastrointestinal absorption, brain penetration, renal reabsorption, defining clearance mechanisms and drug-drug interactions. Passive diffusion rate is translatable across tissues and animal species, while the extent of absorption is dependent on drug properties, as well as in vivo physiology/pathophysiology. Design principles have been developed to guide medicinal chemistry to enhance absorption, which combine the bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 104 publications
0
54
0
Order By: Relevance
“…Cell permeability is also required for compounds to be absorbed after oral administration. 4 Interestingly, some studies have found that macrocyclization can result in major increases in cell permeability, 5 , 6 while others have found only a limited increase 7 , 8 or a reduction in permeability upon macrocyclization. 9 …”
mentioning
confidence: 99%
“…Cell permeability is also required for compounds to be absorbed after oral administration. 4 Interestingly, some studies have found that macrocyclization can result in major increases in cell permeability, 5 , 6 while others have found only a limited increase 7 , 8 or a reduction in permeability upon macrocyclization. 9 …”
mentioning
confidence: 99%
“…Physical chemistry plays a central role in oral drug absorption [86]. In addition, physical chemistry is also important for hepatic clearance, renal clearance, and tissue distribution (including the brain) [85,[168][169][170][171][172][173][174][175][176]. A recent survey suggested that a poor understanding of physical chemistry is one of the reasons for the prediction failure of OA PBPK modelling [6].…”
Section: The Critical Role Of Physical Chemistry In Oa-pbpk Modellingmentioning
confidence: 99%
“…MW, nHBA and nHBA: The molecular weight (MW) plays a pivotal role in the drug action: the higher the MW (500 g/mol ≤ MW), the poorer the absorption and bioavailability 35 . The MW of phytol and 3-tetradecyn-1-ol were calculated and the results are shown in Table 3.…”
Section: Fig 1: a Gc-ms Chromatogram Peak Profile Of Methanolic Encephalartos Ferox Fruit Extractmentioning
confidence: 99%